Effect of excess zinc and arbuscular mycorrhizal fungus on bioproduction and trace element nutrition of Tomato (Solanum lycopersicum L. cv. Micro-Tom). Issue 3 (4th May 2018) - Ibiang, Young Bassey; Innami, Haruki; Sakamoto, Kazunori
ABSTRACT: The effect of excess Zn and arbuscular mycorrhizal (AM) fungus on bioproduction and trace element nutrition were investigated in tomato. In a completely randomized factorial design, the experimental treatments – Zn addition at 0 (normal) and 300 (excess) mg Zn kg −1 soil, and AM inoculation (non-AM and Rhizophagus irregularis ) – were set up in a growth chamber for 10 weeks. Generally, AM effects on the available Zn, Mn, Cu, and Fe in the rhizosphere soil were in tandem with the effects in host tissues. Under normal Zn condition, AM enhanced Cu availability in the rhizosphere, optimized the Cu:Zn balance in shoots, and increased the host biomass production. Excess Zn reduced mycorrhizal colonization in AM plants and the total plant biomass in both AM and non-AM plants. Although AM decreased the Zn concentrations in soil and host tissues under excess Zn, the distortions in host TE balance were not significantly ameliorated by the fungus. While Zn in fruit was within the safety threshold, Mn deficiency in the fruit was observed under excess Zn, alongside increased root-to-fruit Fe and Cu translocations. Mycorrhizal reductions in soil and tissue Mn concentrations were considered a minus in terms of probable symbiont amelioration of Mn:Zn in-balance under excess Zn. Additional microbe(s) that can enhance Mn homeostasis might be helpful in tomato under elevated soil Zn.